If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3y + -3 = 7y + 17 + -2y Reorder the terms: 4 + -3 + 3y = 7y + 17 + -2y Combine like terms: 4 + -3 = 1 1 + 3y = 7y + 17 + -2y Reorder the terms: 1 + 3y = 17 + 7y + -2y Combine like terms: 7y + -2y = 5y 1 + 3y = 17 + 5y Solving 1 + 3y = 17 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 1 + 3y + -5y = 17 + 5y + -5y Combine like terms: 3y + -5y = -2y 1 + -2y = 17 + 5y + -5y Combine like terms: 5y + -5y = 0 1 + -2y = 17 + 0 1 + -2y = 17 Add '-1' to each side of the equation. 1 + -1 + -2y = 17 + -1 Combine like terms: 1 + -1 = 0 0 + -2y = 17 + -1 -2y = 17 + -1 Combine like terms: 17 + -1 = 16 -2y = 16 Divide each side by '-2'. y = -8 Simplifying y = -8
| 1/2y-5/3=-5/7 | | 3x+30=3x+6 | | 2(10x+2)-6(x+2)=-36 | | x*(x+2)=143 | | 3x+30=3x+2 | | 7x+4=2x+19l | | 5x-q=2x-7 | | y*(y+3)=88 | | -2(z+3)-z=-4(z+2) | | 60=20t+5t(2) | | f(x)=0.07(175)+0.12x | | Z^4+2*Z^2+2=0 | | 3x+.8y=5 | | Z^4+2*Z^2-2=0 | | -a+-7+-9a+-2a+-10= | | -3=5.7 | | 11-8y+16=x+12y-2x | | 5d=36.6 | | 5k-10-8k=-35 | | 30=-2+4x | | X=Y^3-14y^2+45y | | 13/3x11/5 | | 2(3x)-5=22 | | 4x^2+16*x=20 | | 324.09=9(0.08m+26.70+0.10(26.70)) | | 4(w+2)-7w=14 | | 12x=7y+3 | | 5*w^2+10*w=40 | | 7xy^4+14x^3y^2= | | X^2-8x+y^2+2y=28 | | 2(7+10c)= | | 3*m*2p= |